Integration of the Resource-Based View, Resource Dependence Theory, Dynamic Capabilities, Social Cognitive Theory, and Firm Performance Theory in Explaining the Performance of Digital MSMEs in Indonesia - Ade Alfarisi; Yayan Hendayana (Dinasti Publisher, 2025)
Digital transformation has changed the global business landscape and requires Micro, Small, and Medium Enterprises (MSMEs) in Indonesia to strengthen their competitiveness through resource-based strategies and adaptive innovation. This article aims to integrate five key theories in strategic management to explain the performance of digital MSMEs, namely: (1) Firm Performance Theory, which assesses organizational success multidimensionally through the Balanced Scorecard; (2) Resource-Based View (RBV), which emphasizes the importance of valuable, rare, difficult to imitate, and organized resources; (3) Resource Dependence Theory (RDT), which highlights the management of external dependencies on suppliers, customers, and institutions; (4) Dynamic Capabilities (DC), which explains the process of sensing, seizing, and reconfiguring resources to adapt to environmental changes; and (5) Social Cognitive Theory (SCT), which emphasizes the role of self-efficacy and collective efficacy as drivers of entrepreneurs’ innovative behavior. The literature review shows that RBV provides an internal foundation, RDT connects organizations with external resources, DC serves as a bridge for strategic adaptation, SCT provides behavioral microfoundation, and performance theory provides a measure of organizational success. This article identifies research gaps in multi-level and longitudinal integration and proposes a research agenda based on a mediation-moderation model to strengthen the performance and sustainability of digital MSMEs in Indonesia.